2015
DOI: 10.1017/s0007114515000446
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated acute salivary α-amylase responses to gustatory stimulation with citric acid in thin children

Abstract: Salivary a-amylase (sAA) is responsible for the 'pre-digestion' of starch in the oral cavity and accounts for up to 50 % of salivary protein in human saliva. An accumulating body of literature suggests that sAA is of nutritional importance; however, it is still not clear how sAA is related to individual's nutritional status. Although copy number variations (CNV) of the salivary amylase gene (AMY1) are associated with variation in sAA levels, a significant amount of sAA variation is not explained by AMY1 CNV. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
5
23
0
Order By: Relevance
“…It is well known that gustatory stimulation with acid promotes salivary secretion, so acute responses of salivary glands induced by acid stimulation can provide more pathophysiological information compared with sole assessment of resting saliva. For example, our previous study found that acute sAA activity response to acid stimulation was reduced in low‐BMI children compared with normal‐BMI children; however, no relationship of nutritional status with sAA activities under both resting and stimulated conditions was found . Hence, our present study focused on acute salivary biochemical characteristic responses to acid stimulation, in order to explore more pathophysiological information of CNAG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known that gustatory stimulation with acid promotes salivary secretion, so acute responses of salivary glands induced by acid stimulation can provide more pathophysiological information compared with sole assessment of resting saliva. For example, our previous study found that acute sAA activity response to acid stimulation was reduced in low‐BMI children compared with normal‐BMI children; however, no relationship of nutritional status with sAA activities under both resting and stimulated conditions was found . Hence, our present study focused on acute salivary biochemical characteristic responses to acid stimulation, in order to explore more pathophysiological information of CNAG.…”
Section: Discussionsupporting
confidence: 93%
“…Our data revealed that attenuated acute sAA activity response to acid stimulation reflects that the extent of sAA response to diet feeding may be decreased and then affect CNAG patients' nutritional status. This suggests that sAA response to acid stimulation may be of nutritional importance, consistent with our previous results …”
Section: Discussionmentioning
confidence: 99%
“…Fifty-five subjects were enrolled, ranging in age from 21 As determined by PD sampling, compared to baseline, the SFR, pH, sAA activity and sTAPM increased significantly (p < 0.05) for both genders after the initial acid stimulation (Table 1). In the PD samples, the mean pH values of females both before and after acid stimulation were significantly lower than males (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, gustatory stimulation, especially acid stimulation, plays a major role in elevated SFR and altered salivary composition [10,11,21,22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These components, whether molecule, transcript, protein, metabolite, or microbe, are reflective of both the age and developmental stage of the individual (25–27). For example, salivary enzymes, such as amylase, are known to increase from early infancy through adolescence, ultimately peaking in adulthood (2831). Salivary electrolyte levels are also known to vary with age.…”
Section: Salivary Variation Across the Pediatric Age Spectrummentioning
confidence: 99%